Modulation of mucosal antiviral immune response at the female genital tract by immunobiotic lactic acid bacteria - Vizoso Pinto, María Guadalupe (2013)
The female genital tract (FGT) has unique characteristics, which have evolved to adequately carry on its vital function of reproduction. Thus, on the one hand the FGT has to be tolerogenic enough not to reject the allogeneic sperm and fetus in order to ensure procreation and; on the other hand it should be reactive enough for clearing viral, bacterial, fungal and parasitic pathogens. To increase complexity, there is a constant exposure of mucosal cells to an endogenous microbiota [1-3], and to the direct and indirect action of sexual hormones (estradiol and progesterone) [4]. The immunity of the FGT has not been studied as extensively as the immunity of the gut, and the antiviral response at this important mucosal site is even less understood. In line with this, immune modulation by lactic acid bacteria (LAB) offers a brand new field of research. In this review, we discuss some recent advances in the understanding of viral infections at the FGT, the use of TLR-ligands as possible therapeutic tools, and the hallmarks during the infection process, which may be used for modulation of the antiviral responses using immunobiotic and/or recombinant LAB expressing viral antigens.